Monetary Policy Transmission Mechanisms and Inflation in Slovakia - Kuijs, Louis (IMF Working Papers; Working Paper, 2002)
This paper presents the results of an empirical analysis into monetary policy transmission mechanisms and inflation in the Slovak Republic. The estimated vector autoregression (VAR) model suggests that inflation is determined by changes in foreign prices, the exchange rate, and wage costs, with a modest effect of aggregate demand, in line with theory for small, open economies. Monetary policy is shown to affect inflation via these channels. Changes in money supply seem to have a modest but rapid impact on prices. The measured effect of interest rate changes is modest and gradual, although it appears to have become more important in recent years.